دراسة مقارنة مخبريّه بين الرّاتنج المركّب النّانومتري والرّاتنج المركّب الهجين من حيث التسرّب الحفافي - حداد منذر; عثمان طارق (Latakia University Journal -Medical Sciences Series, 2017)
هدف البحث : تهدف هذه الدراسة المخبرية إلى تحري معدّل التسرّب الحفافي للرّاتنج المركّب النّانومتري و الرّاتنج المركّب الهجين و المقارنة بينهما . طرائق البحث و مواده : تألّفت العينة من 40 ضاحك سليم مقلوع لأغراض تقويميّة , تمّ تهيئة حفر من الصّنف الخامس بأبعاد ثابتة على السّطح الدّهليزي, قُسمت العينة إلى مجموعتين المجموعة A رُممت بالرّاتنج المركّب النّانومتري ( Z350 ) , المجموعةB رُممت بالرّاتنج المركّب الهجين (Z250 ) , وُضعت العينات ضمن الحاضنة الحراريّة لمدة شهر مع التّعريض لدورات حراريّة , ثم غُمست العينات بأزرق الميتلين 0,5% لمدة 24 ساعة, و أُجريت مقاطع طوليّة (دهليزيّة حنكيّة ) , ودُرس التسرّب الحفافي الحاصل تحت المكبّرة . النتائج : أظهرت الدراسة الإحصائية عدم وجود فروق هامّة إحصائياً في التسرّب الحفافي لكل من الرّاتنج المركّب النّانومتري و الرّاتنج المركّب الهجين . The aim : This study aims to evaluate and compare the microleakage between nano and hybrid composite. Materials and Methods : the sample consisted of forty extracted premolars for orthodontics purposes , class v cavities were prepared with a specific dimensions on the buccal surface. The sample divided into two groups ; group A restored by nanocomposite ( Z350) , group B restored by hybrid composite ( Z250) , after that, the samples were placed in the incubator with thermo cycling for a month ,The samples were then immersed in 0.5 % methelyne blue dye for 24 hours , each tooth was mesial-distal sectioned vertically , finally, of all samples was studied using stereomicroscope to evaluated the microleakage . Results : there was no statistical significant difference between the nano and hybrid composite according to microleakage.